DISEMINASI DAN BEDAH BUKU PENGANTAR MICROTEACHING SEBAGAI UPAYA PENINGKATAN KOMPETENSI MAHASISWA CALON GURU - Khasanah, Uswatun; Isnaini, Isnaini; Sabrina, Farizka Devi Adhelia (Jurnal Indonesia Mengabdi, 2025)
This community service activity aims to enhance the pedagogical and professional competence of pre-service teachers through the dissemination and book review of Introduction to Microteaching by Uswatun Khasanah (Revised Edition, Tahta Media, 2024). The program was carried out using a participatory approach through three main stages: preparation, implementation, and evaluation. The preparation stage included coordination among the organizing team, scheduling, and the development of evaluation instruments; the implementation stage involved material presentations, interactive discussions, and reflective microteaching practices; while the evaluation stage focused on assessing improvements in participants’ understanding and teaching skills. The results showed a significant increase in participants’ comprehension of microteaching concepts, lesson design abilities, and self-confidence in classroom teaching practice. Furthermore, the activity fostered a culture of collaboration, strengthened pedagogical literacy, and broadened the participants’ understanding of reflective teaching as an essential component of professional development. In conclusion, this dissemination and book review activity effectively contributed to strengthening the professional competence of pre-service teachers and served as a model of community service integrating academic literacy with capacity building in higher education.